Right‐wing populism as a social representation: A comparison across four European countries - Staerklé, Christian; Green, Eva G.T. (Journal of community & applied social psychology, 2018)
The rise of right‐wing populist parties has been widely discussed across the social sciences during the last decade. Taking a social representational approach, we analyse organising principles and anchoring of right‐wing populist thinking across four European countries (France, the Netherlands, Switzerland, and the United Kingdom). Using European Social Survey data (Round 7), we compare political attitudes and self‐appraisals of citizens identifying with right‐wing populist, conservative right‐wing, and traditional left‐wing parties. The findings converge across the four countries to show that right‐wing populist identifiers diverge from both left‐ and right‐wing identifiers on vertical (between the “people” and the “elite”) and horizontal (between nationals and immigrants) dimensions of differentiation. Depending on the context, right‐wing populist identification was fuelled by material and physical insecurity, low political efficacy, and distrust of fellow citizens. We conclude that right‐wing populism requires multiple strategies of differentiation within and between groups to justify and sustain itself.